RISIKO ERGONOMI POSTUR KERJA PADA PROSES PENJEMURAN RUMPUT LAUT MENGGUNAKAN METODE NOVEL ERGONOMIC POSTURAL ASSESSMENT DENGAN PERSPEKTIF MACROERGONOMIC ANALYSIS OF STRUCTURE - Mohamad, Silvana; Sri Deviyanti, I Gusti Ayu; Dewi, Sinta; Tranggono, Tranggono (Heuristic, 2024)
Dusun Babana is one of the districts with the majority of people whose main livelihood is as seaweed farmers. The processing process takes 30 days, 45 days to 60 days. In the drying process, it takes 1.5 hours at the earliest and 3 hours at the longest depending on the amount of seaweed being dried. After cleaning seaweed, farmers often complain of pain in their backs and waists. Macroergonomy as an approach with personal subsystems in this case is culture. Work culture is a value that becomes a habit in a group until it manifests itself as an action called a work habit. This work habit causes workers to suffer from musculoskeletal disorders. NERPA as an ergonomic method that works to evaluate the work posture of the upper body so that it can see the work posture that causes the effect on complaints of musculoskeletal disorders. The final score obtained shows at level 4 which means it is required to take action as soon as possible at that very moment. Some improvement measures to minimize the ergonomic risk of work posture include good work techniques and time management.